Fibre optic interconnecting devices and passive components. Performance standard. Non-connectorised single-mode bidirectional 1310 nm upstream and 1490 nm downstream WWDM devices for category O. Uncontrolled environment Part 087-6, (31st May 2012) - British Standards Institution,
No abstract available